Examining The Impact of Islamic Corporate Governance, Doctoral-Level Sharia Supervisory Board, Sharia Compliance, and Board of Commissioners on Fraud Mitigation in Corporate Settings - Fakhruddin, Iwan; Kusbandiyah, Ani; Winarni, Dwi; Norwani, Norlia Mat (Riset Akuntansi dan Keuangan Indonesia, 2025)
ACFE Indonesia in 2025 confirmed that most of the surveyed cases occurred because internal employees exploited weak controls. Employees who committed fraud occurred at all levels, namely operational staff/employees were most involved, especially in the procurement function with 29.3 cases, operational employees with 17.4% of cases, and finance (13.6%). At the middle manager/executive level, there were around 14.3% of cases and at the top management (directors/board) with 6.5% of cases. This study aims to examine the influence of the variables of Islamic Corporate Governance, Shariah Compliance Disclosure, Board of Commissioners, Shariah Supervisory Board Education on internal fraud, using total assets as a control variable. This study uses secondary data from the annual reports of Islamic Commercial Banks accessed on the official websites of each bank. The data collection technique used a purposive sampling method with the criteria of Indonesian Islamic Commercial Banks in the period 2015-2024 and has data related to the term of office of directors, educational background of the DPS, and awards received by Islamic banks. The number of samples obtained was 72 observational data. The analytical method used in this study was panel data regression analysis processed using Stata 17 software. The results showed that Sharia Compliance Disclosure has a significant negative effect on Internal Fraud. And the variables of Islamic Corporate Governance, Board of Commissioners, and Education of the Sharia Supervisory Board do not have a significant effect on Internal Fraud